Advancements in molecular marker development and their applications in the management of biotic stresses in peanuts. (November 2015) - Mishra, Gyan P.; Radhakrishnan, T.; Kumar, Abhay; Thirumalaisamy, P.P.; Kumar, Narendra; Bosamia, Tejas C.; Nawade, Bhagwat; Dobaria, Jentilal R.
Abstract: Peanut is grown extensively in different parts of world, where various biotic and abiotic factors limit its productivity and quality. The major fungal biotic constraints to peanut production include rust ( Puccinia arachidis Speg.), stem-rot ( Sclerotium rolfsii ), collar-rot ( Aspergillus niger Van Teighem), afla-root ( Aspergillus flavus ), and late leaf spot ( Phaeoisariopsis personata Ber. and M A Curtis), while viral disease constraints are peanut bud necrosis disease (PBND) caused by peanut bud necrosis virus (PBNV) and peanut stem necrosis disease (PSND) caused by tobacco streak virus (TSV). Since, only a few sources of resistance are available in cultivated peanut for some diseases, which has resulted in the limited success of conventional breeding programmes on disease resistance. Moreover, even marker assisted breeding in peanut is in the nascent stage and identification of some major quantitative trait loci (QTLs) for a few fungal disease resitance genes has only recently been reported. Substantial efforts are underway to develop PCR-based markers for the construction of high-density genetic linkage maps. This will enable the breeders to effectively pyramid various biotic stress resistance genes into different agronomically superior breeding populations, in a much shorter time. It is expected that the availability of various cost-effective genomic resources (SNPs, whole genome sequencing, KASPar, GBS etc.) and more effective mapping populations (NAM, MAGIC etc.) in the coming years will accelerate the mapping of complex traits in peanut. This review provides an overview of the current developments and future prospects of molecular marker development and their applications for improving biotic-stress resistance in peanut crop. Highlights: In peanut, many markers were associated with various biotic stress resistance QTLs. Peanut genome sequencing is going to place the markers on specific chromosomes. Transgenic peanut lines, resistant to biotic stresses have not yet released commercially. In peanut, genome wide selection must await the development of economical assays. Peanut cultivars, developed using biotechnological tools will be released soon.